The relationship between preseason upper extremity function, pain, and training and normalized Division III collegiate swimming performance - Tate, A. R.; Woznicki, L.; Strouse, G.; Wisseman, D.; Thomas, S. (Journal of Athletic Training, 2025)
Context Shoulder injuries comprise the largest proportion of swimming injuries, and a large percentage of swimmers participate with pain. Therefore, it is assumed that shoulder pain decreases performance, but researchers have not compared collegiate swimmers` performance with and without pain.